The Use of Osteotomies in Nasal Profileplasty - Berkhout, Maaike Cornelia; Menger, Dirk Jan (Facial Plastic Surgery, 2019)
In rhinoplasty, osteotomies are performed to manipulate the bony nasal vault to improve the function and/or the aesthetics of the nose. This article provides an overview of the instruments used for osteotomies, as well as the indications and techniques for osteotomies in nasal profileplasty.
Keywords: rhinoplasty; osteotomy; profileplasty